Electronic and Optoelectronic Applications Based on 2D Novel Anisotropic Transition Metal Dichalcogenides - Gong, Chuanhui; Zhang, Yuxi; Chen, Wei; Chu, Junwei; Lei, Tianyu; Pu, Junru; Dai, Liping; Wu, Chunyang; Cheng, Yuhua; Zhai, Tianyou; Li, Liang; Xiong, Jie (Advanced science, 2017)
With the continuous exploration of 2D transition metal dichalcogenides (TMDs), novel high‐performance devices based on the remarkable electronic and optoelectronic natures of 2D TMDs are increasingly emerging. As fresh blood of 2D TMD family, anisotropic MTe2 and ReX2 (M = Mo, W, and X = S, Se) have drawn increasing attention owing to their low‐symmetry structures and charming properties of mechanics, electronics, and optoelectronics, which are suitable for the applications of field‐effect transistors (FETs), photodetectors, thermoelectric and piezoelectric applications, especially catering to anisotropic devices. Herein, a comprehensive review is introduced, concentrating on their recent progresses and various applications in recent years. First, the crystalline structure and the origin of the strong anisotropy characterized by various techniques are discussed. Specifically, the preparation of these 2D materials is presented and various growth methods are summarized. Then, high‐performance applications of these anisotropic TMDs, including FETs, photodetectors, and thermoelectric and piezoelectric applications are discussed. Finally, the conclusion and outlook of these applications are proposed. The recent research progresses of low‐symmetry MTe2 (M = Mo, W) and ReX2 (X = S, Se) are presented with an emphasis on the crystalline structure, preparation methods, and novel electronic and optoelectronic applications.